Compact and high sensitivity low‐temperature sensor based on coreless silica fiber Mach‐Zehnder interferometer. Issue 8 (15th June 2018) - Baharin, N. F.; Musa, S. M. A.; Azmi, A. I.; Razak, M. A. A.; Abdullah, A. S.; Salim, M. R.; Mohd Noor, M. Y.
Abstract: An all‐fiber Mach‐Zehnder interferometer based on symmetrical offset coreless silica fiber (CSF) is proposed and demonstrated for temperature sensing. The sensor is constructed by a symmetrical offset splicing of a short CSF section between two CSF sections. Thus, two distinct optical paths are created inside and outside of the offset section resembling a Mach‐Zehnder interferometer. For temperature sensing, the offset gap is filled with refractive index liquid with high thermo‐optic coefficient of 3.34 × 10 −4 . Measurement is established by monitoring wavelength shift resulting from interference of modes between the two distinct optical paths. A very high temperature sensitivity of 3220 pm/°C has been achieved with a short sensor length of 1.5 mm. Due to its compact size and high sensitivity, the proposed structure would be an attractive option for low temperature measurement such as for human body temperature monitoring.